2016
DOI: 10.1158/0008-5472.can-15-2812
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 Drives Melanoma Growth by Stimulating Mesenchymal Stromal Cell–Induced Angiogenesis and M2 Polarization of Tumor-Associated Macrophages

Abstract: Secretion of the powerful angiogenic factor MFG-E8 by pericytes can bypass the therapeutic effects of anti-VEGF therapy, but the mechanisms by which MGF-E8 acts are not fully understood. In this study, we investigated how this factor acts to promote the growth of melanomas which express it. We found that mouse bone marrow-derived mesenchymal stromal cells (MSC) expressed a substantial amount of MFG-E8. To assess its expression from this cell type we implanted melanoma cells and MSC derived from wild-type (WT) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 44 publications
7
75
1
Order By: Relevance
“…28,29 In addition, we previously determined that hypoxia stimulation enhanced the synthesis of MFG-E8 in vascular endothelial cells and pericytes in vivo and in vitro, and that MFG-E8 expression in the skin of mice with ischemiareperfusion injury was enhanced in vivo. 12,13 Collectively, elevated serum MFG-E8 levels may play protective roles against cerebrovascular diseases, including ischemic cerebral infarction in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 In addition, we previously determined that hypoxia stimulation enhanced the synthesis of MFG-E8 in vascular endothelial cells and pericytes in vivo and in vitro, and that MFG-E8 expression in the skin of mice with ischemiareperfusion injury was enhanced in vivo. 12,13 Collectively, elevated serum MFG-E8 levels may play protective roles against cerebrovascular diseases, including ischemic cerebral infarction in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Furthermore, interactions of MFG-E8 with integrin aV have also been implicated in the regulation of various functions, such as angiogenesis and mammary gland branching. 5,6,[10][11][12][13][14] With respect to SLE and MFG-E8, it has been reported that serum MFG-E8 levels are higher in SLE patients compared with in healthy controls. [15][16][17] A positive correlation between serum MFG-E8 levels and immune complex level was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overexpression of MFG-E8 is negatively associated with prognosis in various cancers including breast, colorectal and esophageal cancers [83][84][85]. According to Yamada et al, MFG-E8 promotes angiogenesis by upregulating the expression of VEGF and endothelin (ET)-1 in bone marrow-derived mesenchymal stromal cells to trigger tumor progression in melanomas [86]. Besides, MFG-E8 enhances M2 polarization of macrophages [86,87], and blockade of MFG-E8 enhances antitumor effector T cells but inhibits Treg cells, leading to tumor destruction [17].…”
Section: Bridging Moleculesmentioning
confidence: 99%
“…In response to stimulation with these cytokines, melanoma cells produce angiogenic factors, including IL-8, VEGF, TIE2 and CD31, which results in neoangiogenesis (29,41). Furthermore, the proangiogenic factor released by pericytes-milk fat globule-epidermal growth factor 8 stimulates the polarization of M2 macrophages, suggesting that they also increase tumor angiogenesis (42).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 99%